Safety and Tolerability of COVID-19 Vaccination in Adolescents and Young Adults with Epilepsy: A Multicenter Questionnaire Study - Kobayashi, Yoshiyuki; Ishikawa, Nobutsune; Tateishi, Yuichi; Izumo, Hiroki; Eguchi, Yuta; Fujii, Yuji; Ono, Hiroaki; Okada, Satoshi (Journal of Pediatric Epilepsy, 2023)
Background Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 and was first recorded in December 2019. COVID-19 became a pandemic involving almost all countries, including Japan. We evaluated the tolerability and safety of coronavirus vaccines in terms of seizures in adolescents and young adults with epilepsy (AYAWE).Methods We administered a questionnaire to AYAWE who visited the pediatrics departments of Hiroshima University Hospital, Hiroshima Prefectural Hospital, and Hiroshima City Funairi Citizens Hospital in January and February 2022. Tolerability and safety after immunization were assessed.Results In total, 114 vaccinations were delivered to 57 AYAWE aged 12 to 25 years (mean, 15 ± 3.1 years). Fifty-two (91.2%) experienced more than or equal to 1 adverse event postvaccination. The most commonly reported adverse events were fever (dose 1, 33.3%; dose 2, 73.7%) and fatigue (dose 1, 24.6%; dose 2, 50.9%). The incidences of headache (5.2 vs. 21.0%, p = 0.024), fever (33.3 vs. 73.7%, p < 0.001), and fatigue (24.6 vs. 50.9%, p = 0.004) differed significantly between the first and second doses. Only 5.2% of patients experienced transient seizure worsening, and only one patient reported a change in seizure semiology.Conclusion COVID-19 vaccines were well-tolerated in our cohort. The vaccines did not affect the number or manifestations of seizures. Similar to other illnesses, vaccination for COVID-19 can be administered to AYAWE without worsening their seizures.
Keywords: epilepsy; COVID-19; vaccination; adolescents; young adults